REGIONALIZATION OF THE IDF CURVE FOR THE PROVINCES OF LOS RÍOS, GUAYAS AND EL ORO. (LACCEI, 2024)
The small amount of information in the country regarding precipitation intensity parameters, generates the present research, which aims to present the analysis of the parameters k, m and n belonging to the Bernard equation for the development of Intensity, Duration and Frequency (IDF) curves, using the regionalization method with historical data from different meteorological stations located in Ecuador, specifically in the provinces of Los Rios, Guayas, El Oro and neighboring areas. Regionalization allows us to obtain data from projections based on information obtained through interpolation methods, the best known being ordinary kriging (KO) and inverse distance weighting (IDW), with which a comparison will be made to choose the one that has the highest degree of affinity with the provinces mentioned above and their meteorological data. The regionalization allows the development of the present model, which is reliable in areas where the available data is poor and the meteorological stations do not cover efficiently. The results provided by the KO method had better adjustment in the study provinces, presenting error percentages for Los Rios, Guayas 1, Guayas 2, Guayas 3 and El Oro of 0,92%, 7,64%, 14,21%, 19,83% and 4,47% for parameter k and 13,72%, 19,14%, 1,74%, 8,40% and 6,76% for parameter m respectively, being parameter n constant, it was omitted in the analysis.